Literature Review: The Positive Impact of Murottal Al-Qur'an Therapy on Anxiety in Hemodialysis Patients - Zamsiah Martiasih; Dwi Retno Sulistyaningsih; Suyanto Suyanto; Erna Melastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hemodialysis patients often experience anxiety that impacts quality of life and requires effective intervention. Murottal therapy has the potential to be an alternative to reduce anxiety, can be recommended as part of holistic care that is easy to apply and has minimal side effects for hemodialysis patients. Objectives: This literature review aims to evaluate the positive impact of Qur'anic murottal therapy on anxiety in hemodialysis patients. Methods: This study used a literature study of journal articles. Articles were searched through Google Scholar, PubMed, ResearchGate, and Semantic Scholar with the keywords “Hemodialysis”, “Anxiety”, and “Murottal Al-Qur'an” using the PCC approach. The PRISMA flowchart details the article selection process: initial identification of 462 articles, elimination of 203 duplications, exclusion of 185 articles based on irrelevant titles and abstracts, leaving 18 articles. 8 articles were again excluded after full text assessment as they did not meet the inclusion criteria. The selection process resulted in 10 final articles that met the inclusion criteria: national and international journal articles in Indonesian and English, published in 2019-2024, free full text available, and discussing murottal therapy for hemodialysis patient anxiety. Results: Out of hundreds of articles, ten articles showed consistent results that Qur'anic murottal therapy is effective in reducing the anxiety level of hemodialysis patients. Conclusion: Based on the literature analysis, Qur'anic murottal shows a positive impact as an effective therapy in overcoming anxiety in hemodialysis patients.